Tubercular Palmar Ganglion Presenting as a Severe Carpal Tunnel Syndrome – A Case Report - Pravendra Singh; Shristi Singh; Abhishek Singh; Nikhil Relwani; Samay Das; Suraj Sood (Journal of Orthopaedic Case Reports)
Introduction: Tuberculous tenosynovitis is a rare condition predominantly found in developing countries that require prompt medical intervention. Due to its atypical presentation, diagnosis through biopsy and culture is necessary to distinguish it from other diseases. Compound palmar ganglion is an unusual manifestation that can cause swelling around the wrist joint and potentially compress the neural structures, resulting in carpal tunnel syndrome. Case Report: A 27-year-old female, homemaker complained of pain and tingling sensations in her right hand. Radiological analysis revealed juxta-articular osteopenia with soft tissue swelling. Magnetic resonance imaging identified a spongy soft tissue lesion compressing the median nerve over the flexor retinaculum of the right wrist. The decision was to surgically explore and excise the lesion along with carpal tunnel release. Histopathological examination confirmed tubercular tenosynovitis. Conclusion: Tubercular compound ganglion is a rare condition that must be kept in mind while treating patients with carpal tunnel syndrome, especially in developing countries where tuberculosis is prevalent. Delayed diagnosis is common due to gradual progression and subtle symptoms except for swelling. Surgical intervention and antitubercular treatment are crucial components of compound palmar ganglion management. Early diagnosis and management are essential for preventing complications.